1993
DOI: 10.1152/ajpendo.1993.265.2.e284
|View full text |Cite
|
Sign up to set email alerts
|

Plasma NE concentrations do not accurately reflect sympathetic nervous system activity in human sepsis

Abstract: Plasma norepinephrine concentrations ([NE]) when raised in patients with sepsis are thought to indicate increased activity of the sympathetic nervous system (SNS). However, increased SNS activity may occur without a concomitant rise in plasma [NE]. Measurement of NE kinetics (clearance and spillover) is a more accurate and direct assessment of SNS activity. In the present study plasma [NE] and NE kinetics were measured in six patients with intra-abdominal sepsis (septic) using tritiated NE infused to achieve a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 8 publications
3
25
0
Order By: Relevance
“…Accordingly, it is plausible that part of the prognostic utility of CgA in severe sepsis can be attributed to CgA representing an index of overall adrenergic activity. This may have clinical relevance as circulating catecholamine concentrations fail to accurately reflect adrenergic tone in patients with sepsis [30]. Moreover, the strict pre-analytical handling, the large day-to-day variations, and the cumbersome and time-consuming, sophisticated methods required for analysis of catecholamines make the use of adrenaline and noradrenalin analyses impractical for routine clinical use [31].…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, it is plausible that part of the prognostic utility of CgA in severe sepsis can be attributed to CgA representing an index of overall adrenergic activity. This may have clinical relevance as circulating catecholamine concentrations fail to accurately reflect adrenergic tone in patients with sepsis [30]. Moreover, the strict pre-analytical handling, the large day-to-day variations, and the cumbersome and time-consuming, sophisticated methods required for analysis of catecholamines make the use of adrenaline and noradrenalin analyses impractical for routine clinical use [31].…”
Section: Discussionmentioning
confidence: 99%
“…Sustained SNS activation during sepsis [295][296][297], including increased gut-derived NE release [298] may have either beneficial or detrimental consequences. Ablation of the SNS prior to gram-negative bacteria challenge, such as Listeria monocytogenes, Pseudomonas aeruginosa or Escherichia coli, reduces bacterial dissemination [299][300][301][302].…”
Section: Sympathetic Activation and Endotoxic Shock: Inflammatory Andmentioning
confidence: 99%
“…The increases not only may alter the immune function but also may contribute to host morbidity and increased risk of infection (1,7,34). In the current study we reexamined the in vitro growth responses of a variety of bacterial species that were previously tested and reported not to be enhanced by the addition of NE (6,8).The conditions employed in this study include a minimally nutritive low-iron medium previously shown to maintain bacteriostasis (21), a low initial inoculum density of bacteria (10 CFU/ml) in order to capture the lag phase of the bacterial growth curve typically observed in a bacteriostatic medium (21,26), and a concentration of NE (0.0001 M) (14, 15, 26) which corresponds to target tissue levels and not mere plasma spillover (16,18,20). These rigorous conditions better represent in vivo milieus and also allow more suitable evaluation of a growth enhancement effect without the camouflage of rapid bacterial growth encountered when rich medium and large inocula are employed.…”
mentioning
confidence: 99%